Effects of cowdung and potassium on growth and yield of Kohlrabi (Journal of the Bangladesh Agricultural University, 2012)
An experiment was carried out at the Horticulture Farm of the Bangladesh Agricultural University, Mymensingh during  the period from November 2010 to January 2011 to study the effects of cowdung and potassium on growth and yield  of Kohlrabi. The experiment consisted of three levels of cowdung (0, 20 and 40 t/ha) and four levels of potassium (0,  20, 50, 80 kg /ha). The experiment was laid out in randomized complete block design with three replications. All the  parameters were significantly influenced by application of cowdung and potassium. The highest plant height (44.65  cm), number of leaves per plant (12.11), length of largest leaf (37.54 cm), and breadth of largest leaf (18.66 cm) were  obtained from the highest dose of cowdung and potassium applied (40 t cowdung + 80 kg K/ha) while the lowest  plant height (33.64 cm), number of leaves (9.01), length of largest leaf (27.94 cm), and breadth of largest leaf (11.00  cm) were obtained from control treatment combination. The highest fresh weight of leaves (49.33 g), fresh weight of  knob (328.66 g) and fresh weight of roots (66.55 g) per plant were also recorded under the treatment combination of  40 t cowdung + 80 kg K/ha, while the lowest fresh weight of leaves (22.11 g), fresh weight of knob (136.00 g) and  fresh weight of roots (23.33 g) were obtained from control treatment combination. Similarly, the dry weight of leaves  (19.34%), knob (15.19%) and roots (32.75%) were highest under the same treatment combination of 40 t cowdung +  80 kg K/ha and the lowest dry weight of leaves (11.71%), dry weight of knob (7.38%) and dry weight of roots  (15.29%) were obtained from control treatment combination C0K0. The marketable yields of knob per plot (7.86 kg)  and per hectare (39.58 tons) were also the highest under the treatment combination 40 t cowdung/ha and 80 kg  potassium per hectare.   DOI: http://dx.doi.org/10.3329/jbau.v10i1.12035   J. Bangladesh Agril. Univ. 10(1): 2732, 2012